PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) BERBASIS PROBLEM SOLVING PADA MATA PELAJARAN KIMIA SMA POKOK BAHASAN KOLOID - Fika Risvita; Betty Holiwarni; Johni Azmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This Research aims to develop Student Worksheet Based on ProblemSolving in Colloid of Chemistry in Senior High School Subject in terms of valid basedon the feasibility aspect of content, language, serve and graphic. This type of researchis research and development (R and D) with reference to the development process of 4-D model. The subject of this research is student worksheet based on problem solving.Instrument of data collection are validation given by three validators, and from analysisof data obtained by the validity aspect of content, language, serving and graphicconsecutively by 90%, 83.33%, 88.33% and 95.83% with valid category. Based on theresults of data analysis can be concluded that the Activity Sheet Students (LKPD) basedproblem solving generated declared valid and can be used on subjects SMA subject ofcolloid chemistry. Based on the results of data analysis can be concluded that studentworksheet based on problem solving has been valid and can be used in Senior HighSchool Chemistry Subject of colloid.Keywords: Colloid, Problem Solving, Student Worksheet